Nonaqueous electrolyte secondary battery

By forming a double-layer structure of lithium metal compound and boron compound on the surface of lithium transition metal composite oxide particles, the problem of rising resistance of nonaqueous electrolyte secondary batteries in high temperature environments is solved, and the stability and performance of battery resistance are improved.

CN119133384APending Publication Date: 2024-12-13PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411142629.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-01-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Non-aqueous electrolyte secondary batteries are prone to rise in resistance in high-temperature environments, and it is difficult for the prior art to effectively suppress the increase in the initial resistance and high-temperature cycle.

Method used

The first layer composed of lithium metal compound is formed on the surface of lithium transition metal composite oxide particles, and the second layer composed of boron compound is covered, forming a solid coating of M and boron to suppress side reactions of nonaqueous electrolytes and metals in the positive electrode. Dissolve and reduce battery resistance.

Benefits of technology

The initial resistance is successfully reduced and the rise of the resistance is effectively suppressed under high-temperature cycle conditions, improving the performance stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133384A_ABST
    Figure CN119133384A_ABST
Patent Text Reader

Abstract

In a nonaqueous electrolyte secondary battery, a positive electrode has a positive electrode active material (A). The positive electrode active material (A) contains: a lithium transition metal composite oxide represented by general formula LiaNibCocMndAleMfOg (in the formula, M is at least one element selected from group 4, group 5, and group 6, 0.8 < = a < = 1.2, b > = 0.82, 0 lt; c < = 0.08, 0.05 < = d < = 0.12, 0 < = e < = 0.05, 0.01 < = f < = 0.05, and 1 < = g < = 2); a first layer comprising a lithium metal compound represented by general formula LixMyOz (in the formula, 1 < = x < = 4, 1 < = y < = 5, and 1 < = z < = 12), the first layer being formed on the particle surface of the lithium transition metal composite oxide; and a second layer comprising a boron compound and formed on the first layer. The first layer is formed on the surface of the particles of the lithium transition metal composite oxide throughout the entire region thereof without interposing the second layer.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application filed on January 27, 2020, with application number 202080018312.9 and invention name “Non-aqueous electrolyte secondary battery”. Technical Field

[0002] The present disclosure relates to a nonaqueous electrolyte secondary battery, and more particularly to a nonaqueous electrolyte secondary battery including a lithium transition metal composite oxide as a positive electrode active material. Background Art

[0003] In the past, in order to improve battery performance such as storage characteristics, it is known that there are positive electrode active materials in which other compounds exist on the particle surface of lithium transition metal composite oxide. For example, Patent Document 1 discloses a positive electrode active material, which is manufactured by roasting in a state where a compound of a specified element (TiO2, etc.) of an element of Group 4 to Group 6 whose oxide has a melting point of 750°C or above is present on the particle surface of lithium transition metal composite oxide. In addition, Patent Document 2 discloses a positive electrode active material, which is manufactured by roasting in a state where a boric acid compound exists on the particle surface of lithium transition metal composite oxide, wherein the content of carbonate ions is less than 0.15% by weight, and the content of borate ions is 0.01% by weight to 5.0% by weight.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2004-253305

[0007] Patent Document 2: Japanese Patent Application Publication No. 2010-040382 Summary of the invention

[0008] However, in non-aqueous electrolyte secondary batteries, it is required to reduce the charge transfer resistance in the positive electrode and suppress the initial resistance of the battery to a low level. In addition, when the non-aqueous electrolyte secondary battery is charged and discharged under a high temperature environment, it is easy to cause an increase in resistance, but suppressing the above-mentioned resistance increase is an important issue. The purpose of the present disclosure is to provide: a non-aqueous electrolyte secondary battery with a low initial resistance that can suppress the resistance increase during high temperature cycles.

[0009] A nonaqueous electrolyte secondary battery as one embodiment of the present disclosure comprises: an electrode body including a positive electrode, a negative electrode and a separator; and a nonaqueous electrolyte, wherein the positive electrode at least comprises a positive electrode active material A. The positive electrode active material A comprises: a lithium transition metal composite oxide having a general formula of Li a Ni b Co c Mn d Ale M f O g (wherein, M is at least one element selected from Group 4, Group 5 and Group 6, 0.8 ≤ a ≤ 1.2, b ≥ 0.82, 0 < c ≤ 0.08, 0.05 ≤ d ≤ 0.12, 0 ≤ e ≤ 0.05, 0.01 ≤ f ≤ 0.05, 1 ≤ g ≤ 2); the first layer is composed of a lithium metal compound represented by the general formula Li x M y O z (wherein, 1 ≤ x ≤ 4, 1 ≤ y ≤ 5, 1 ≤ z ≤ 12), and is formed on the surface of the particles of the aforementioned lithium transition metal composite oxide; and, the second layer is composed of a boron compound and is formed on the aforementioned first layer, and the aforementioned first layer is formed on the surface of the particles of the aforementioned lithium transition metal composite oxide throughout its entire area without intervening the aforementioned second layer.

[0010] According to the non-aqueous electrolyte secondary battery as one embodiment of the present disclosure, an increase in battery resistance during high-temperature cycling can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 FIG. is a perspective view of a non-aqueous electrolyte secondary battery as an example of an embodiment.

[0012] Figure 2 FIG. is a perspective view of an electrode body as an example of an embodiment.

[0013] DESCRIPTION OF REFERENCE NUMERALS

[0014] 10 Non-aqueous electrolyte secondary battery

[0015] 11 Exterior body

[0016] 12 Accommodation part

[0017] 13 Sealing part

[0018] 14 Electrode body

[0019] 15 Positive electrode lead

[0020] 16 Negative electrode lead

[0021] 20 Positive electrode

[0022] 21 Positive electrode tab

[0023] 22 Positive electrode tab laminated part

[0024] 30 Negative electrode

[0025] 31 Negative electrode tab

[0026] 32 Negative electrode tab laminated part

[0027] 40 Dividers DETAILED DESCRIPTION

[0028] It is known that by making the general formula Li x M y O z The lithium metal compound shown is present on the particle surface of the lithium transition metal composite oxide, thereby reducing the initial resistance of the battery. It is believed that the lithium metal compound functions as a lithium ion conductor, which is beneficial to reducing the charge transfer resistance of the positive electrode. On the other hand, when the lithium metal compound is present on the particle surface of the lithium transition metal composite oxide, the increase in battery resistance during high temperature cycling cannot be suppressed, and sometimes the resistance is increased.

[0029] By forming a first layer composed of a lithium metal compound and a second layer composed of a boron compound and covering the first layer on the particle surface of the lithium transition metal composite oxide, the inventors succeeded in reducing the initial resistance and suppressing the resistance increase during high-temperature cycling. It is believed that due to the presence of the second layer of the boron compound covering the first layer, a strong coating containing M and boron is formed on the particle surface of the positive electrode active material during high-temperature cycling, thereby suppressing the side reaction of the non-aqueous electrolyte in the positive electrode and the dissolution of the metal in the positive electrode active material, and suppressing the increase in battery resistance.

[0030] Hereinafter, an example of an embodiment of the nonaqueous electrolyte secondary battery of the present disclosure will be described in detail. Hereinafter, a nonaqueous electrolyte secondary battery 10 is illustrated in which a wound electrode body 14 is housed in an outer body 11 formed of a laminate sheet, but the outer body is not limited thereto, and may be, for example, an outer can in a cylindrical, square, or coin shape. In addition, the electrode body may be a laminated electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated with separators therebetween.

[0031] Figure 1 1 is a perspective view showing the appearance of a non-aqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 In the example, the nonaqueous electrolyte secondary battery 10 includes an outer body 11 composed of two laminate films 11A and 11B. In addition, the nonaqueous electrolyte secondary battery 10 includes an electrode body 14 and a nonaqueous electrolyte housed in the outer body 11. The outer body 11 includes, for example, a housing portion 12 having a substantially rectangular shape in plan view and housing the electrode body 14 and the nonaqueous electrolyte, and a sealing portion 13 formed around the housing portion 12. The laminate films 11A and 11B are generally composed of a resin film containing a metal layer such as aluminum.

[0032] The housing portion 12 may be provided by forming a recess capable of housing the electrode body 14 in at least one of the laminate films 11A and 11B. Figure 1In the example shown, the recess is formed only in the laminate film 11A. The sealing portion 13 is formed by bonding the peripheral edges of the laminate films 11A and 11B to each other. Figure 1 In the illustrated example, the sealing portion 13 is formed in a frame shape with substantially the same width so as to surround the housing portion 12 .

[0033] The nonaqueous electrolyte secondary battery 10 includes a pair of electrode leads (a positive electrode lead 15 and a negative electrode lead 16 ) connected to the electrode body 14 . Figure 1 In the illustrated example, the positive electrode lead 15 and the negative electrode lead 16 are led out from the same end of the exterior body 11 to the outside of the exterior body 11 .

[0034] The non-aqueous electrolyte includes: a non-aqueous solvent, and an electrolyte salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent include esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. The non-aqueous solvent may contain a halogen-substituted body in which a portion of the hydrogen of these solvents is replaced by a halogen atom such as fluorine. It should be noted that the non-aqueous electrolyte is not limited to a liquid electrolyte, and may also be a solid electrolyte using a gel-like polymer or the like. Examples of the electrolyte salt include lithium salts such as LiPF6.

[0035] Figure 2 FIG. 1 is a perspective view of an electrode body 14 as an example of an embodiment. Figure 2 In the example, the electrode body 14 is a wound electrode body including a positive electrode 20, a negative electrode 30 and a separator 40, wherein the positive electrode 20 and the negative electrode 30 are spirally wound with the separator 40 interposed therebetween and formed into a flat shape. The positive electrode 20 has a positive electrode tab 21 which is a convex portion of a portion of the electrode plate protruding in the axial direction of the electrode body 14. Similarly, the negative electrode 30 has a negative electrode tab 31 protruding in the same direction as the positive electrode tab 21. A plurality of positive electrode tabs 21 and negative electrode tabs 31 are formed at constant intervals in the longitudinal direction of each electrode plate.

[0036] The electrode body 14 is formed as follows: the positive electrode 20 and the negative electrode 30 are overlapped and wound with the separator 40 interposed therebetween so that the positive electrode tabs 21 and the negative electrode tabs 31 are alternately arranged along the longitudinal direction of the electrode plate. In the electrode body 14, the positive electrode tabs 21 overlap each other and the negative electrode tabs 31 overlap each other, and a positive electrode tab laminated portion 22 is formed at one end in the width direction of the electrode body 14, and a negative electrode tab laminated portion 32 is formed at the other end in the width direction. It should be noted that the positive electrode lead 15 is welded to the positive electrode tab laminated portion 22, and the negative electrode lead 16 is welded to the negative electrode tab laminated portion 32.

[0037] Hereinafter, the positive electrode 20 , the negative electrode 30 , and the separator 40 constituting the electrode body 14 , particularly the positive electrode 20 , will be described in detail.

[0038] [positive electrode]

[0039] The positive electrode 20 has: a positive electrode core, and a positive electrode composite material layer disposed on the surface of the positive electrode core. The positive electrode core can use a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 20, a thin film of the metal disposed on the surface, and the like. The positive electrode composite material layer preferably contains a positive electrode active material, a conductive material, and a binding material, and is disposed on both sides of the positive electrode core except for the portion to which the positive electrode lead 15 is connected. The positive electrode 20 can be made, for example, as follows: a positive electrode composite material slurry containing a positive electrode active material, a conductive material, and a binding material is applied to the surface of the positive electrode core, and after the coating is dried, it is compressed to form a positive electrode composite material layer on both sides of the positive electrode core, thereby being made.

[0040] As the conductive material contained in the positive electrode composite material layer, carbon materials such as carbon black, acetylene black, Ketjen black, and graphite can be exemplified. As the binding material contained in the positive electrode composite material layer, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. These resins can be used in combination with cellulose derivatives such as carboxymethyl cellulose (CMC) or its salts, polyethylene oxide (PEO), etc.

[0041] The positive electrode composite material layer has at least a positive electrode active material A as a positive electrode active material. The positive electrode active material A includes: a lithium transition metal composite oxide; a first layer composed of a lithium metal compound and formed on the surface of particles of the lithium transition metal composite oxide; and a second layer composed of a boron compound and formed on the first layer. The positive electrode active material A is a secondary particle formed by the aggregation of primary particles. The first layer is formed on the surface of the particles of the lithium transition metal composite oxide throughout its entire area and without the second layer.

[0042] The positive electrode active material A includes lithium transition metal composite oxide / first layer / second layer in order from the inside of the particle. That is, the positive electrode active material A can be said to be a core-shell particle having a shell formed by the first layer and the second layer on the surface of the core particle formed by the lithium transition metal composite oxide. By forming the first layer formed by the lithium metal compound on the surface of the secondary particle of the lithium transition metal composite oxide, the initial resistance of the battery can be reduced, and by forming the second layer formed by the boron compound covering the first layer, the increase in battery resistance during high temperature cycling can be suppressed.

[0043] The lithium transition metal composite oxide constituting the positive electrode active material A (hereinafter sometimes referred to as "lithium transition metal composite oxide A") has a general formula Li a Ni b Co c Mn d Al e M f O gComposite oxide represented by (wherein M is at least one element selected from Group 4, Group 5, and Group 6 elements, 0.8 ≤ a ≤ 1.2, b ≥ 0.82, 0 < c ≤ 0.08, 0.05 ≤ d ≤ 0.12, 0 ≤ e ≤ 0.05, 0.01 ≤ f ≤ 0.05, 1 ≤ g ≤ 2). The content rate of Ni is preferably 82 to 92 mol%, more preferably 82 to 90 mol%, relative to the total molar number of metal elements other than Li.

[0044] In the lithium transition metal composite oxide A, the content of Co is preferably 3 to 8 mol%, more preferably 5 to 8 mol%, relative to the total molar number of metal elements other than Li. If the content of Co is higher than 8 mol%, the increase in resistance during high-temperature cycling cannot be suppressed. In addition, the content of Mn is preferably 6 to 10 mol% relative to the total molar number of metal elements other than Li. If the content of Mn is lower than 5 mol%, the increase in resistance during high-temperature cycling cannot be suppressed. It should be noted that the lithium transition metal composite oxide A may contain elements other than Li, Ni, Co, Mn, and M within the scope that does not impair the purpose of the present disclosure.

[0045] The above-mentioned first layer is composed of a lithium metal compound represented by the general formula Li x M y O z (wherein 1 ≤ x ≤ 4, 1 ≤ y ≤ 5, 1 ≤ z ≤ 12). The first layer can be formed so as to cover the entire surface area of the secondary particles of the lithium transition metal composite oxide A, or can be dispersed on the particle surface.

[0046] M in the above general formula is at least one element selected from Group 4, Group 5, and Group 6 elements, preferably at least one selected from Ti, Nb, W, and Zr. That is, the lithium transition metal composite oxide A preferably contains at least one selected from Ti, Nb, W, and Zr. In addition, the lithium metal compound constituting the first layer preferably contains at least one selected from Ti, Nb, W, and Zr. Suitable lithium metal compounds are, for example, Li2TiO3, Li4Ti5O 12 , LiTiO4, Li2Ti2O5, LiTiO2, Li3NbO4, LiNbO3, Li4Nb2O7, Li8Nb6O 19 , Li2ZrO3, LiZrO2, Li4ZrO4, Li2WO4, Li4WO5.

[0047] Regarding the content rate of the first layer, based on the element of M in the above general formula, it is preferably 0.001 to 1 mol%, more preferably 0.01 to 0.5 mol%, relative to the total molar number of metal elements other than Li in the positive electrode active material A. If the content rate of the first layer is within this range, it becomes easier to suppress the increase in battery resistance during high-temperature cycling.

[0048] As described above, the second layer is composed of a boron compound and is formed on the first layer. The second layer preferably covers the entire area of ​​the first layer. That is, the first layer is preferably not exposed on the surface of the positive electrode active material A. In the case where the first layer is dispersed on the particle surface of the lithium transition metal composite oxide A, a portion of the second layer can be directly formed on the particle surface of the lithium transition metal composite oxide A. The second layer can be formed by, for example, covering the entire area of ​​the secondary particle surface of the lithium transition metal composite oxide A including the area where the first layer is formed.

[0049] The second layer is not formed between the secondary particle surface of the lithium transition metal composite oxide A and the first layer, but is formed only on the surface facing the opposite side of the lithium transition metal composite oxide A to the first layer. In addition, the lithium metal compound constituting the first layer and the boron compound constituting the second layer are not mixed with each other, and the boundary between the first layer and the second layer can be confirmed by XPS, for example.

[0050] The boron compound constituting the second layer is not particularly limited as long as it is a compound containing B, and is preferably an oxide or a lithium oxide. As an example of a boron compound, boron oxide (B2O3), lithium borate (Li2B4O7), etc. can be cited. The content of the second layer is preferably 0.1 to 1.5 mol%, more preferably 0.5 to 1.0 mol%, relative to the total molar number of metal elements other than Li in the positive electrode active material A, based on the boron element. If the content of the second layer is within this range, it becomes easy to suppress the increase in battery resistance during high temperature cycling.

[0051] The average primary particle size of the positive electrode active material A is, for example, 100 nm to 1000 nm. In addition, the average particle size (average secondary particle size) of the positive electrode active material A is, for example, 8 μm to 15 μm. It should be noted that the particle size of the positive electrode active material A is substantially equal to the particle size of the lithium transition metal composite oxide A.

[0052] The average primary particle size of the positive electrode active material is obtained by analyzing the SEM image of the particle cross section observed by a scanning electron microscope (SEM). For example, the positive electrode 20 or the positive electrode active material is embedded in a resin, a cross section is made by a cross section polisher (CP), and the cross section is photographed with an SEM. 30 random primary particles are selected from the SEM image to observe the grain boundaries of the primary particles. Then, based on the shape of a specific primary particle, the long diameter (longest diameter) of each of the 30 primary particles is obtained, and their average value is used as the average primary particle size.

[0053] The average secondary particle size can also be obtained from the SEM image of the particle cross section. Specifically, 30 secondary particles are randomly selected from the above SEM image, and the grain boundaries of the selected 30 secondary particles are observed. Then, based on the appearance of the specific secondary particles, the major diameter (longest diameter) of each of the 30 secondary particles is obtained, and their average value is used as the average secondary particle size.

[0054] The positive electrode active material A is produced, for example, by the following steps.

[0055] (1) A nickel-cobalt-manganese composite hydroxide is calcined at 400° C. to 600° C. to obtain a nickel-cobalt-manganese composite oxide.

[0056] (2) mixing the composite oxide, a lithium compound such as lithium hydroxide, and a compound containing a metal element selected from Group 4, Group 5, and Group 6 at a predetermined molar ratio, and calcining the mixture at 700° C. to 900° C. in an oxygen atmosphere to obtain Li x M y O z The lithium metal compound (first layer) shown is a precursor fixed to the surface of particles of a lithium transition metal composite oxide.

[0057] (3) The precursor and a boron compound are mixed at a predetermined molar ratio and calcined in an oxygen atmosphere at 150° C. to 400° C.

[0058] The positive electrode 20 preferably has positive electrode active material A and positive electrode active material B as positive electrode active materials. Positive electrode active material B, like positive electrode active material A, is preferably a secondary particle formed by aggregation of primary particles. The average primary particle size of positive electrode active material B is greater than 0.5 μm and greater than the average primary particle size of positive electrode active material A. The average primary particle size of positive electrode active material B is, for example, 0.5 μm to 4 μm. In addition, the average secondary particle size of positive electrode active material B is 2 μm to 7 μm and less than the average secondary particle size of positive electrode active material A. Positive electrode active material B may be composed only of primary particles instead of secondary particles. By using positive electrode active material B in combination, the resistance increase during high temperature cycling can be further suppressed.

[0059] The lithium transition metal composite oxide constituting the positive electrode active material B (hereinafter sometimes referred to as “lithium transition metal composite oxide B”) has the general formula Li a Ni b Co c Mn d M e O f(In the formula, M is at least one element selected from Group 4, Group 5 and Group 6 elements, 0.8 ≤ a ≤ 1.2, b ≥ 0.80, 0 < c ≤ 0.15, 0 < d ≤ 0.15, 0 ≤ e ≤ 0.05, 1 ≤ f ≤ 2) the composite oxide shown. The lithium transition metal composite oxide B may have the same composition as the lithium transition metal composite oxide A. It should be noted that the amount of Co in the positive electrode active material B is preferably equal to or more than the amount of Co in the positive electrode active material A.

[0060] The positive electrode active material B preferably includes a surface layer composed of the general formula Li x M y O z (In the formula, 1 ≤ x ≤ 4, 1 ≤ y ≤ 5, 1 ≤ z ≤ 12) the lithium metal compound shown, and is formed on the surface of the secondary particles of the lithium transition metal composite oxide B. This surface layer is the layer corresponding to the first layer of the positive electrode active material A, and can be formed so as to cover the entire surface area of the secondary particles of the lithium transition metal composite oxide B, or can be dispersed on the particle surface. M in the above general formula is at least one element selected from Group 4, Group 5 and Group 6 elements, preferably at least one element selected from Ti, Nb, W and Zr. Suitable lithium metal compounds are Li2TiO3, Li4Ti5O 12 、LiTiO4, Li2Ti2O5, LiTiO2, Li3NbO4, LiNbO3, Li4Nb2O7, Li8Nb6O 19 , Li2ZrO3, LiZrO2, Li4ZrO4, Li2WO4, Li4WO5.

[0061] The content rate of the surface layer in the positive electrode active material B is preferably lower than the content rate of the first layer in the positive electrode active material A. The content rate of the surface layer is preferably 0.001 to 1.0 mol%, more preferably 0.01 to 0.5 mol% based on the element standard of M in the above general formula with respect to the total number of moles of the metal elements other than Li in the positive electrode active material B. The ratio of the content rate of the first layer in the positive electrode active material B to the content rate of the first layer in the positive electrode active material A is preferably 1.1 or more.

[0062] The positive electrode active material B preferably further includes a second surface layer formed on the above surface layer. The second surface layer is the layer corresponding to the second layer of the positive electrode active material A and is composed of a boron compound. The second surface layer preferably covers the entire area of the above surface layer (hereinafter referred to as "the first surface layer"). When the first surface layer is dispersed on the particle surface of the lithium transition metal composite oxide B, a part of the second surface layer can be directly formed on the particle surface of the lithium transition metal composite oxide B.

[0063] The second surface layer is not formed between the secondary particle surface of the lithium transition metal composite oxide B and the first surface layer, but is formed only on the surface facing the opposite side of the lithium transition metal composite oxide A to the first surface layer. That is, the first surface layer is formed on the particle surface of the lithium transition metal composite oxide B over its entire area without the second surface layer.

[0064] The boron compound constituting the second surface layer is not particularly limited as long as it is a compound containing B, and is preferably an oxide or a lithium oxide. As an example of a boron compound, boron oxide (B2O3), lithium borate (Li2B4O7), etc. can be cited. The content of the second surface layer in the positive electrode active material B may be lower than the content of the second layer in the positive electrode active material A. The content of the second layer is preferably 0.1 to 1.5 mol%, more preferably 0.5 to 1.0 mol%, based on the boron element, relative to the total molar number of metal elements other than Li in the positive electrode active material B.

[0065] The positive electrode active material B is produced, for example, by the following steps.

[0066] (1) A nickel-cobalt-manganese composite hydroxide is calcined at 400° C. to 600° C. to obtain a nickel-cobalt-manganese composite oxide.

[0067] (2) mixing the composite oxide, a lithium compound such as lithium hydroxide, and a compound containing a metal element selected from Group 4, Group 5, and Group 6 at a predetermined molar ratio, further adding an alkali component such as potassium hydroxide at a predetermined concentration, and calcining the mixture at 650° C. to 850° C. in an oxygen atmosphere to obtain Li x M y O z The lithium metal compound (first surface layer) shown is a precursor of a lithium transition metal composite oxide particle fixed to the surface.

[0068] (3) The precursor and a boron compound are mixed at a predetermined molar ratio and calcined in an oxygen atmosphere at 150° C. to 400° C.

[0069] [negative electrode]

[0070] The negative electrode 30 includes: a negative electrode core, and a negative electrode composite material layer disposed on the surface of the negative electrode core. The negative electrode core may be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 30, or a thin film having the metal disposed on the surface. The negative electrode composite material layer preferably includes a negative electrode active material and a binding material, and is disposed on both sides of the negative electrode core except for the portion connected to the negative electrode lead 16. The negative electrode 30 may be manufactured, for example, by coating a negative electrode composite material slurry including a negative electrode active material and a binding material on the surface of the negative electrode core, drying the coating, and then compressing the coating to form negative electrode composite material layers on both sides of the negative electrode core.

[0071] The negative electrode composite material layer includes, for example, a carbon-based active material that reversibly absorbs and releases lithium ions as a negative electrode active material. Suitable carbon-based active materials are natural graphites such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite (MAG), and graphitized mesophase carbon microbeads (MCMB) and other artificial graphites. In addition, the negative electrode active material can use a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material can be used in combination.

[0072] The binder contained in the negative electrode composite material layer may be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode 20, preferably styrene-butadiene rubber (SBR). In addition, the negative electrode composite material layer preferably further comprises CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, SBR, CMC or its salt, PAA or its salt are suitably used in combination.

[0073] [Separator]

[0074] The separator 40 uses a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, non-woven fabrics, etc. Suitable materials for the separator 40 are polyolefins such as polyethylene and polypropylene, cellulose, etc. The separator 40 may be a single-layer structure or a laminated structure. A heat-resistant layer may be formed on the surface of the separator.

[0075] Example

[0076] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.

[0077] <Example 1>

[0078] [Synthesis of Positive Electrode Active Material A]

[0079] The nickel-cobalt-manganese composite hydroxide obtained by coprecipitation is calcined at 500°C to obtain a nickel-cobalt-manganese composite oxide. Next, the composite oxide is mixed with lithium hydroxide and zirconium oxide (ZrO2) in such a manner that the total amount of Ni, Co, and Mn and the molar ratio of Li to Zr are 1:1.08:0.01. The mixture is calcined in an oxygen atmosphere at 800°C for 20 hours and crushed to obtain a positive electrode active material precursor. The precursor is mixed with boric acid (H3BO3) in such a manner that the total amount of Ni, Co, and Mn and the molar ratio of B are 1:0.01, and the mixture is calcined in an oxygen atmosphere at 300°C for 3 hours to obtain a positive electrode active material A in which the surface of the above-mentioned lithium metal compound (first layer) is covered with a boron compound (second layer).

[0080] By ICP, it was confirmed that the composition of the positive electrode active material A is Li 1.03 Ni 0.85 Co 0.08 Mn 0.07 Zr 0.01 O2. The average primary particle size of the positive electrode active material A was 800 nm, and the average particle size (average secondary particle size) was 12.1 μm.

[0081] [Production of positive electrode]

[0082] The positive electrode active material A, acetylene black and polyvinylidene fluoride (PVdF) were mixed in a mass ratio of 96.3:2.5:1.2, and N-methyl-2-pyrrolidone (NMP) was used as a dispersion medium to prepare a positive electrode composite material slurry. Next, the positive electrode composite material slurry was applied to both sides of a positive electrode core formed of aluminum foil, and the coating was dried and compressed, and then cut into a specified electrode size to produce a positive electrode having a positive electrode composite material layer formed on both sides of the positive electrode core.

[0083] [Production of negative electrode]

[0084] Natural graphite is used as the negative electrode active material. The negative electrode active material is mixed with sodium salt of carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) at a mass ratio of 100:1:1, and water is used as a dispersion medium to prepare a negative electrode composite material slurry. Next, the negative electrode composite material slurry is applied to both sides of the negative electrode core formed by copper foil, and after the coating is dried and compressed, it is cut into a specified electrode size to produce a negative electrode with a negative electrode composite material layer formed on both sides of the negative electrode core.

[0085] [Preparation of non-aqueous electrolyte]

[0086] LiPF6 was dissolved at a concentration of 1 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 3:3:4. Furthermore, vinylene carbonate (VC) was dissolved at a concentration of 2% by mass in the mixed solvent to prepare a non-aqueous electrolyte.

[0087] [Battery production]

[0088] The positive electrode with an aluminum positive electrode lead and the negative electrode with a nickel negative electrode lead were spirally wound through a polyethylene separator and formed into a flat shape to produce a wound electrode body. The electrode body was housed in an outer body composed of an aluminum laminate, and the non-aqueous electrolyte was injected, and the opening of the outer body was sealed to produce a 650mAh non-aqueous electrolyte secondary battery.

[0089] <Example 2>

[0090] In the synthesis of positive electrode active material A, titanium oxide (TiO2) is used instead of ZrO2, and nickel-cobalt-manganese composite oxide, lithium hydroxide and titanium oxide (TiO2) are mixed in a manner such that the total amount of Ni, Co, and Mn and the molar ratio of Li to Ti become 1:1.08:0.03. Apart from this, a non-aqueous electrolyte secondary battery is prepared in the same manner as in Example 1.

[0091] <Example 3>

[0092] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that niobium oxide (Nb2O5) was used instead of ZrO2 in the synthesis of the positive electrode active material A.

[0093] <Example 4>

[0094] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that tungsten oxide (WO 3 ) was used instead of ZrO 2 in the synthesis of the positive electrode active material A.

[0095] <Example 5>

[0096] [Synthesis of positive electrode active material B]

[0097] The nickel-cobalt-manganese composite hydroxide obtained by coprecipitation was calcined at 500°C to obtain a nickel-cobalt-manganese composite oxide. Next, the composite oxide was mixed with lithium hydroxide and TiO2 in such a manner that the total amount of Ni, Co, and Mn and the molar ratio of Li to Ti were 1:1.08:0.03. Furthermore, 10% by mass of potassium hydroxide was added to the mixture, and the mixture was calcined at 750°C for 40 hours in an oxygen atmosphere, and then crushed, washed with water, and dried to obtain a positive electrode active material B.

[0098] By ICP, it was confirmed that the composition of the positive electrode active material B is Li 1.03 Ni 0.85 Co 0.08 Mn 0.07 Ti 0.03 O2. The average primary particle size of the positive electrode active material B was 2 μm, and the average secondary particle size was 5 μm.

[0099] In the preparation of the positive electrode, a nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 2 except that a mixture of the positive electrode active material A and the positive electrode active material B at a mass ratio of 7:3 was used as the positive electrode active material.

[0100] <Example 6>

[0101] In the synthesis of positive electrode active material B, a nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 4 except that nickel-cobalt-manganese composite oxide, lithium hydroxide and titanium oxide were mixed so that the total amount of Ni, Co and Mn and the molar ratio of Li to Ti were 1:1.08:0.01.

[0102] <Example 7>

[0103] [Synthesis of positive electrode active material B]

[0104] The nickel-cobalt-manganese composite hydroxide obtained by coprecipitation is calcined at 500°C to obtain a nickel-cobalt-manganese composite oxide. Next, the composite oxide is mixed with lithium hydroxide and TiO2 in such a manner that the total amount of Ni, Co, and Mn and the molar ratio of Li to Ti are 1:1.08:0.01. Further, potassium hydroxide is added to the mixture at 10% by mass, and after being calcined at 750°C for 40 hours in an oxygen atmosphere, it is crushed, washed with water, and dried to obtain a positive electrode active material precursor. The precursor is mixed with H3BO3 in such a manner that the total amount of Ni, Co, and Mn and the molar ratio of B are 1:0.01, and the mixture is calcined at 300°C for 3 hours in an oxygen atmosphere to obtain a positive electrode active material B in which the surface of the above-mentioned lithium metal compound (first surface layer) is covered with a boron compound (second surface layer). The average primary particle size of the positive electrode active material B is 2μm and the average secondary particle size is 5μm.

[0105] In the preparation of the positive electrode, a nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 2 except that a mixture of the positive electrode active material A and the positive electrode active material B at a mass ratio of 7:3 was used as the positive electrode active material.

[0106] <Comparative Example 1>

[0107] A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 2 except that TiO2 was not mixed in the synthesis of the positive electrode active material A, and mixing of H3BO3 and subsequent calcination were not performed. The average primary particle size of the positive electrode active material A was 740 nm, and the average secondary particle size was 11.1 μm.

[0108] <Comparative Example 2>

[0109] A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 2 except that TiO2 was not mixed in the synthesis of the positive electrode active material A. The average primary particle size of the positive electrode active material A was 740 nm, and the average secondary particle size was 11.1 μm.

[0110] <Comparative Example 3>

[0111] A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 2 except that mixing with H3BO3 and subsequent calcination were not performed in the synthesis of the positive electrode active material A. The average primary particle size of the positive electrode active material A was 740 nm, and the average secondary particle size was 12.1 μm.

[0112] <Comparative Example 4>

[0113] In the synthesis of the positive electrode active material A, a nonaqueous electrolyte secondary battery was produced in the same manner as in Example 2 except that a nickel-cobalt-manganese composite hydroxide was synthesized so that the molar ratio of Ni, Co, and Mn became 0.82:0.12:0.06.

[0114] <Comparative Example 5>

[0115] In the synthesis of the positive electrode active material A, a nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 2 except that the lithium nickel cobalt manganese composite oxide was mixed with TiO2 and H3BO3 and calcined in an oxygen atmosphere at 300°C for 3 hours. The average primary particle size of the positive electrode active material A was 700 nm and the average secondary particle size was 11.8 μm.

[0116] <Comparative Example 6>

[0117] In the synthesis of positive electrode active material A, nickel cobalt manganese composite oxide, lithium hydroxide and H3BO3 were mixed in a manner that the total amount of Ni, Co, and Mn and the molar ratio of Li to B were 1:1.08:0.01, and baked in an oxygen atmosphere at 300°C for 3 hours to obtain a positive electrode active material precursor in which a boron compound was fixed to the particle surface of the lithium transition metal composite oxide. The precursor was mixed with titanium oxide in a manner that the molar ratio of the total amount of Ni, Co, and Mn to Ti was 1:0.03, and the mixture was baked in an oxygen atmosphere at 300°C for 3 hours to obtain positive electrode active material A. A positive electrode was made using the positive electrode active material A, and a non-aqueous electrolyte secondary battery was made in the same manner as in Example 2 except that.

[0118] <Comparative Example 7>

[0119] In the synthesis of positive electrode active material A, tungsten oxide (WO3) is used instead of TiO2, and nickel-cobalt-manganese composite oxide, lithium hydroxide and tungsten oxide (WO3) are mixed in a manner such that the total amount of Ni, Co, and Mn and the molar ratio of Li to W become 1:1.08:0.01. Apart from this, a non-aqueous electrolyte secondary battery is prepared in the same manner as in Comparative Example 3.

[0120] <Comparative Example 8>

[0121] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 4 except that tungsten oxide (WO 3 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0122] <Comparative Example 9>

[0123] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 5 except that tungsten oxide (WO 3 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0124] <Comparative Example 10>

[0125] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 6 except that tungsten oxide (WO 3 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0126] <Comparative Example 11>

[0127] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 3 except that niobium oxide (Nb 2 O 5 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0128] <Comparative Example 12>

[0129] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 4 except that niobium oxide (Nb 2 O 5 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0130] <Comparative Example 13>

[0131] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 5, except that niobium oxide (Nb 2 O 5 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0132] <Comparative Example 14>

[0133] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 6, except that niobium oxide (Nb 2 O 5 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0134] <Comparative Example 15>

[0135] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 3 except that zirconium oxide (ZrO 2 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0136] <Comparative Example 16>

[0137] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 4 except that zirconium oxide (ZrO 2 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0138] <Comparative Example 17>

[0139] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 5 except that zirconium oxide (ZrO 2 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0140] <Comparative Example 18>

[0141] A nonaqueous electrolyte secondary battery was produced in the same manner as in Comparative Example 6 except that zirconium oxide (ZrO 2 ) was used instead of TiO 2 in the synthesis of the positive electrode active material A.

[0142] <Comparative Example 19>

[0143] In the synthesis of the positive electrode active material A, the nickel-cobalt-manganese composite oxide, lithium hydroxide and titanium oxide (TiO2) were mixed in such a manner that the total amount of Ni, Co, and Mn and the molar ratio of Li to Ti were 1:1.08:0.1, and a non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 1. The positive electrode active material A was measured by XRD, and the results confirmed that Li2TiO3 was attached to the surface of the particles of the lithium transition metal composite oxide.

[0144] <Comparative Example 20>

[0145] In the synthesis of positive electrode active material A, nickel-cobalt-manganese composite oxide, lithium hydroxide and niobium oxide (NbO2) were mixed in a manner such that the total amount of Ni, Co, and Mn and the molar ratio of Li to Nb were 1:1.08:0.1, and a nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1. For positive electrode active material A, XRD measurement confirmed that Li3NiO4 was attached to the surface of the particles of the lithium transition metal composite oxide.

[0146] <Comparative Example 21>

[0147] In the synthesis of positive electrode active material A, nickel-cobalt-manganese composite oxide, lithium hydroxide and zirconium oxide (ZrO2) were mixed in a manner such that the total amount of Ni, Co, and Mn and the molar ratio of Li to Zr were 1:1.08:0.1, and a non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 1. For positive electrode active material A, XRD measurement confirmed that Li2ZrO3 was attached to the surface of the particles of the lithium transition metal composite oxide.

[0148] [Evaluation of resistance increase rate after high temperature cycle test]

[0149] For each battery of the embodiment and comparative example, charge at a constant current of 0.5 It until half of the initial capacity is reached at a temperature of 25°C, then stop charging and leave for 15 minutes. After that, charge at a constant current of 0.1 It for 10 seconds, measure the voltage at this time, and then discharge the charge capacity for 10 seconds. Repeat the charge and discharge and voltage measurement at current values ​​of 0.1 It to 2 It. The resistance value is calculated from the relationship between the measured voltage value and current value, and is used as the resistance value before the cycle test.

[0150] The cycle test was carried out under the following conditions, the resistance value after 150 cycles was obtained by the above method, and the increase rate of the resistance value after 150 cycles relative to the resistance value before the cycle test was calculated. The evaluation results are shown in Table 1 as relative values ​​with the increase rate of the battery of Example 1 being 100.

[0151] (Cyclic test)

[0152] Each battery was charged at a constant current of 0.5 It until the battery voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current value reached 1 / 50 It. Thereafter, the battery was discharged at a constant current of 0.5 It until the battery voltage reached 2.5 V. This charge and discharge cycle was repeated 150 times.

[0153] [Table 1]

[0154]

[0155] As shown in Table 1, the resistance increase rate after the high temperature cycle test of the battery of the embodiment is lower than that of the battery of the comparative example. In addition, when the positive electrode active materials A and B are used in combination (refer to Examples 4 to 6), the increase in resistance can be further suppressed. On the other hand, when at least one of the first layer and the second layer is not present on the particle surface of the lithium transition metal composite oxide (Comparative Examples 1 to 3, 7, 11, 15), when there is no layer configuration of particles / first layer / second layer (Comparative Examples 5, 6, 9, 10, 13, 14, 17, 18), and when the lithium transition metal composite oxide does not have a specified composition (Comparative Examples 4, 8, 12, 16), the battery resistance increases significantly after the high temperature cycle test.

Claims

1. A non-aqueous electrolyte secondary battery comprising: an electrode body including a positive electrode, a negative electrode and a separator; and a non-aqueous electrolyte, The positive electrode comprises: a positive electrode active material A and a positive electrode active material B, The positive electrode active material A comprises: A lithium transition metal composite oxide containing Ni, Co and Mn and a metal M consisting of at least one selected from Ti, Nb, W and Zr, wherein the content of Ni is 82 mol% or more relative to the total molar number of metal elements other than Li; a first layer composed of a lithium metal oxide containing the metal M and formed on the surface of particles of the lithium transition metal composite oxide; and a second layer composed of a boron compound and formed on the first layer, The positive electrode active material B contains at least one selected from Ti, Nb, W and Zr, The first layer is formed on the surface of the particles of the lithium transition metal composite oxide over the entire area thereof without interposing the second layer therebetween, The positive electrode active material A and the positive electrode active material B are secondary particles formed by aggregation of primary particles. The average primary particle size of the positive electrode active material B is 0.5 μm or more and larger than the average primary particle size of the positive electrode active material A. The average secondary particle size of the positive electrode active material B is 2 μm to 7 μm, and is smaller than the average secondary particle size of the positive electrode active material A.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The second layer covers the entire area of ​​the first layer.

3. The nonaqueous electrolyte secondary battery according to claim 1, wherein The positive electrode active material B includes a surface layer formed on the surface of the secondary particles, and the surface layer is composed of the general formula Li x M y O z The lithium metal compound shown in the formula, wherein 1≤x≤4, 1≤y≤5, 1≤z≤12, The first layer is composed of the general formula Li x M y O z The lithium metal oxide composition shown in the formula, wherein 1≤x≤4, 1≤y≤5, 1≤z≤12, The content of the surface layer in the positive electrode active material B is lower than the content of the first layer in the positive electrode active material A. The content of the first layer refers to the general formula Li x M y O z The ratio of the molar number of the element M in the positive electrode active material A to the total molar number of the metal elements other than Li, The content of the surface layer refers to the general formula Li x M y O z The ratio of the number of moles of the element M in π to the total number of moles of the metal elements in the positive electrode active material B excluding Li.

4. The nonaqueous electrolyte secondary battery according to claim 3, wherein: The positive electrode active material B includes a second surface layer formed on the surface layer, and the second surface layer is composed of a boron compound.